Cinza vegetal como corretivo e fertilizante na manutenção de pastagem de capim Paiaguás no Cerrado mato-grossense - Silva Filho, Amorésio Souza (2023)
Wood ash is a solid residue from the burning of organic material and can represent an important source of nutrients, in addition to being an alternative destination for this industrial residue. Thus, it was aimed to evaluate the use of wood ash as liming material and fertilizer associated with two application strategies to the soil (not incorporated and incorporated into the soil), in Paiaguás grass pasture in the Cerrado, Mato Grosso state. The experiment was carried out at the Federal University of Rondonópolis and conducted in two consecutive years, corresponding to the pasture maintenance periods (2020-2021 and 2021-2022) of paiaguá grass, which was implanted by sowing in December 2018. The soil is classified as dystrophic Red Latosol. The experiment was set up in a randomized block experimental design, in a 5 x 2 factorial scheme, in strip plot design. The treatments corresponded to five rates of wood ash (0; 8; 16; 24 and 32 t ha-1 ) and two wood ash application strategies (incorporated and not incorporated into the soil), with four replications. Wood ash was applied in November 2018 and reapplied in pasture maintenance in December 2019. Since then, until this research was carried out, no wood ash reapplications were made. Three assessments of the pasture and soil were carried out, with intervals of 30 days between cuts, in the rainy season of each year, with the following response variables: chlorophyll index (SPAD index), plant height (cm), number of leaves (leaves m-2 ), number of tillers (tillers m-2 ), number of leaves per basal tiller, dry mass per tiller (g tiller-1 ), leaf area index (LAI), leaf area per tiller (cm2 tiller-1 ), leaf/stem ratio, dry mass of leaves (t ha-1 ), dry mass of green leaves (t ha-1 ), dry mass of senescent leaves (t ha-1 ), dry mass of stems (t ha-1 ), dry mass productivity (t ha-1 ), and crop growth rate (TAC) (g DM m-2 day-1 ), in addition to soil chemical attributes (pH, Phosphorus; Potassium; Calcium; Magnesium; Aluminum; Hydrogen; Cation exchange capacity at pH 7.0; Organic matter; Sum of bases; Base saturation; Aluminum saturation and Ca/Mg ratio). Data were submitted to analysis of variance and, when significant (p≤0.05), analyzed by Tukey's test for qualitative variables (application strategies) and regression analysis for quantitative variables (wood ash rates), both with statistical probability up to 5%. The increment of wood ash doses positively influenced the soil pH. The best result regarding the development of the pasture was in the second maintenance period (2021) provided a dry mass productivity for the incorporated application of 15.49 t ha-1 , while for the not-incorporated application strategy provided a productivity of 14.02 t ha-1 . The best results regarding the height of the pasture in the second maintenance period (2021), provided greater height in the first cut of 95.55 cm in the incorporated strategy provided in the wood ash dose of 22.11 t ha-1 and height of 101, 45 cm in the not incorporated form observed in the wood ash dose of 20.45 t ha1 . In the following year, in the third maintenance period (2022), the highest height was 71.44 cm in the second cut in the incorporated form provided at a dose of ash of 27.02 t ha-1 and 69.98 cm in the non-incorporated form associated with a rate of ash of 28.06 t ha-1 . The application of wood ash doses from 16 to 32 t ha-1 is responsible for the maximum production in the two years of maintenance of the pasture in the application strategies of incorporated and not incorporated to the soil of the wood ash.